To complete the proof that \( m∠1 + m∠3 + m∠2 = 180° \) given the provided statement, we need to fill in the blanks strategically:
-
From the given information, we can fill in the first blank:
- Fill in the first blank: \( m∠4 \)
- Thus, the complete statement becomes: \( m∠1 + m∠3 + m∠4 = 180° \) by the definition of a straight angle.
-
Now, we will fill in the last blank:
- Fill in the last blank: \( m∠2 \)
- The final statement looks like this: \( m∠1 + m∠3 + m∠2 = 180° \) by substitution.
So the completed proof reads:
Given the diagram shown, \( ∠1 ≅ ∠5; ∠2 ≅ ∠4 \) because alternate interior angles are congruent when lines are parallel. Then, I know that \( m∠1 = m∠5; m∠2 = m∠4 \) because congruent angles have equal measures. \( m∠5 + m∠3 + m∠4 = 180° \) by the definition of a straight angle. Finally, \( m∠1 + m∠3 + m∠2 = 180° \) by substitution.